Labor market impact of disruptions in global value chains - Moritz Meister (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2024)
This paper investigates the causal effect of global value chain (GVC)-related trade on the German labor market during the COVID-19 crisis, using a difference-in-differences approach combined with entropy balancing. The analysis of monthly establishment-level data from January 2019 to December 2021 shows that a one standard deviation increase in GVC-related trade with China leads to an increase in short-time work of up to 27 percentage points, with significant positive effects observed from May to October 2020. For this period, the regression results imply that a one standard deviation increase in GVC integration gives rise to an additional expenditure on short-time work of around 7.3 billion euros. In contrast, GVC-related trade with the whole world as a trading partner does not show a significant impact. Additional survey data support these findings, suggesting that establishments that are more GVC-integrated with China face more difficulties in obtaining inputs or dealing with suppliers in 2020. – – Diese Studie untersucht mit Hilfe eines Differenz-in-Differenzen-Ansatzes in Kombination mit Entropy Balancing den kausalen Effekt von globalen Wertschöpfungsketten (GVC) auf den deutschen Arbeitsmarkt während der COVID-19-Krise. Die Analyse von monatlichen Betriebsdaten von Januar 2019 bis Dezember 2021 zeigt, dass ein Anstieg des GVC-bezogenen Handels mit China um eine Standardabweichung zu einem Anstieg der Kurzarbeit um bis zu 27 Prozentpunkte führt, wobei die Effekte von Mai bis Oktober 2020 signifikant positiv sind. Für diesen Zeitraum würde den Regressionsergebnissen zufolge ein Anstieg um eine Standardabweichung zu zusätzlichen Ausgaben für Kurzarbeit in Höhe von rund 7,3 Milliarden Euro führen. Im Gegensatz dazu ergeben sich für den GVC-bezogene Handel mit der Welt als Handelspartner keine signifikanten Effekte. Zusätzliche Befragungsdaten stützen die Ergebnisse und deuten darauf hin, dass Betriebe, die stärker in GVCs mit China eingebunden sind, im Jahr 2020 mehr Schwierigkeiten bei der Beschaffung von Vorleistungen oder bei der Zusammenarbeit mit Lieferanten hatten.
Keywords: F16; F61; D57; C22; C23; 330; COVID-19 Crisis; German Labor Market; Global Value Chains; Short-Time Work; Difference-in-Differences